BUILDING TRUST IN FAMILY BUSINESS - Agustiono, Agustiono; Wijaya, Carlina (Universitas Ciputra Surabaya, 2018)
This research aims about how to build parent’s trust at Super Rasa Jaya Company. This is a family company engaged in bakery industry. This research was a descriptive qualitative. For data collecting technique, this study used interview and observations method. The data were validated though data validity test. Data triangulation was carried out by interviewing 6 informants who worked as entrepreneurs. Four of them have become a successful leaders of the next generation for more than 5 years. Two others were the owners of Super Rasa Jaya Company. This study found the owner of Super Rasa Jaya Company (head of the generation) had not been able to have their trust on the performance of their future generations yet. To gain that trust, the future generations had to work very hard. They were also required to provide evidence about their work. The next generation had to be able to demonstrate high performance in running and organizing the company. They had to able to produce a variety of new products and improve the quality of production in order to get the trust from the heads of the previous generation.